TANTANGAN ORANG TUA DALAM MENDIDIK ANAK DI ERA DIGITAL MENURUT AMORIS LAETITIA - Sulastika, Paula; Tinenti, Hemma Gregorius; Steven, Laurentinus; Korina, Korina; Kabosu, Evariana Viktoria (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2024)
This research explores the challenges faced by parents in educating children. This research uses an interview method approach. The aim of this research is to look at parents' teaching patterns towards children in the digital era, especially in terms of the use and use of gadgets. This research study is also to illustrate the values of the Amoris Laetitia document regarding joy in the family with the parenting patterns of children. The research results show that parents are still used to their children's rigid needs, lack of consistent discipline, parents who do not understand the dangers of gadgets, so they do not understand the positive and negative impacts of using gadgets. Parents find it difficult to control the social environment and the needs provided by parents are limited to physical needs but there are no spiritual needs. However, this research is far from perfect and there are many shortcomings, therefore future researchers are advised to conduct research in different locations to see whether the results are consistent or whether there are differences that arise due to differences in culture, geography or social conditions, but focus more on Artificial Intelligence (AI), especially its impact on children's education and parenting patterns.